An Empirical Investigation of Capital Structure Strategies Adopted by Botswana Firms – An Exploratory Study - Mapharing, Mogotsinyana; Biza-Khupe, Simangaliso; Sekolokwane, Sadie K. (Archives of Business Research, 2016)
The paper is set on the theoretical backdrop of the importance and exigency of capital structure in firms’ pursuits to maximize shareholders’ wealth. The study investigates the different capital structure strategies adopted by Botswana firms. In its methodology, the study adopted an approach used by <a title="Graham, 2001 #16" href="file:///C:/Users/biza-khu/Desktop/Bizza/Work%20Files/2009/RESEARCH%20PAPERS%20’09/Papers%20’08/Capital%20Structure%20Research/An%20Empirical%20Investigation%20of%20Capital%20Structure%20Strategies%20Adopted%20by%20Botswana%20Firms.docx#_ENREF_1">Graham and Harvey [1] in developing the research instrument. The study methodology used is premised on the presupposition that issues of capital structure are more pronounced with the increase in firm size, with the largest firms generally being those listed on the stock exchange. Primary data was collected from a small sample of firms listed on the Botswana Stock Exchange (BSE), in keeping with the exploratory nature of the study. The results were indicative of lack of theoretical considerations in the adoption and application of capital structure strategies by management across the listed firms. While most firms preferred using external equity as a financing option, followed by retained earnings, debt was found to be the least preferred financing option. Also found was that management was generally knowledgeable of the benefits associated with debt financing, and in particular the tax-deductibility of the cost of debt and reduction of agency costs. Overall, the findings were puzzling when juxtaposed with the theoretical perspectives of the trade-off theory, the pecking order theory and agency costs theory. The study concludes by suggesting further research to uncover the extent to which these preliminary results are applicable and uncovering the underlying rationality.